Left ventricular diastolic reserve by exercise stress echocardiography in prediabetes - Abdulameer Jasim Jawad Al-Gburi (Tzu-Chi Medical Journal, 2023)
Objectives: The objective of this study was to evaluate if the diastolic reserve is different in prediabetes versus control during exercise. Materials and Methods: During the resting stage and graded supine bicycling exertion (25 W, 3 min increment), the mitral inflow and septal mitral annular velocities were determined in 50 patients with prediabetes (21 females, mean age 48 ± 16 years) and 50 gender- and age-matched controls. None demonstrated rest or inducible cardiac ischemia on echocardiography. Results: Between the two study groups, the velocities of the mitral inflow (E) and septal mitral annulus (E′) at rest are not significantly different. E′ during exercise, on the other hand, was significantly lower in individuals with prediabetes than in controls (8.57 ± 2.46 vs. 9.82 ± 2.42 cm/s at 25 W, P = 0.012; 9.42 ± 1.93 vs. 11.15±2.97 cm/s at 50 W, P = 0.001). E/E′ behaves oppositely during exercise with a value that is significantly higher in patients with prediabetes. Conclusion: The diastolic reserve of the left ventricle, as determined by the change in E′ and E/E′ throughout exercise, is abnormal in individuals with prediabetes who do not have overt cardiac disease. Using exercise stress echocardiography may be helpful for the early recognition of subclinical diastolic dysfunction in prediabetics which may have clinical repercussions in the future.